Evaluation of Scymnus nubilus (Coleoptera: Coccinellidae) as a biological control agent against Aphis spiraecola and Cinara juniperi (Hemiptera: Aphididae). Issue 2 (5th September 2019) - Rosagro, Roberto Meseguer; Borges, Isabel; Vieira, Virgilio; Solé, Gemma Pons; Soares, António O
Abstract: BACKGROUND: Aphids are a major insect pest of forestry systems. In this study, we evaluate the potential of the ladybeetle Scymnus nubilus Mulsant (Coleoptera: Coccinellidae) as a biological control agent against Aphis spiraecola Patch and Cinara juniperi (De Geer) (Hemiptera: Aphididae) infesting Azorean endemic plants reared in forestry nurseries. RESULTS: Aphis spiraecola, infesting Viburnum treleasei Gand. (Dipsacales: Adroxaceae), was the most abundant aphid; however, a higher proportion of Juniperus brevifolia (Seub.) Antoine (Pinales: Cupressaceae) was infested by C. juniperi . Scymnus nubilus fourth instar larvae were able to complete development on both aphid species. Voracity was significantly higher when S. nubilus was fed on A. spiraecola but biomass consumption was significantly lower. The relative growth rate and conversion efficiency of the fourth instar larvae were similar. Field experiments indicated that S. nubilus can contribute to the decrease in pest population densities. However, the fourth instar larvae proved to be more efficient when released onto A. spiraecola ; this outcome can be attributed to the distribution patterns of the aphids on the host plant and to the aphid or host plant morphology. Predator density and sleeve cage effect are apparently critical factors in reaching an efficient control. CONCLUSION: The obtained results provide the essential preliminary information required to establish future programs of biological control against aphids infesting Azorean endemic plants. Developmental and feeding performances, as well as the immediate impact of the predator when released onto A. spiraecola colonies, indicate that S. nubilus could be a useful candidate for reducing aphid populations. © 2019 Society of Chemical Industry Abstract : Scymnus nubilus was able to reduce aphid populations infesting Azorean endemic plants by up to 80% when innoculated against A. spiraecola while no significant impact was recorded against C. juniperi .